Oxygen free radicals and veterinary medicine - TSELEPIDIS (Σ. Θ. ΤΣΕΛΕΠΙΔΗΣ) S. (Journal of the Hellenic Veterinary Medical Society, 2018)
Oxygen free radicals have a strong cytotoxic action due to single atoms or groups of atoms that have one or more unpaired electrons. Potentially they can cause damages to several organs of the body and the latest years they have been incriminated for a great number of diseases and many dyndroms in human medicine as well as in veterinary medicine. In the present paper it is presented in general the origin, the biology and the mode of action of oxygen free radicals on the under ischemia and reperfusion